The Deep Learning with Keras Workshop Learn how to define and train neural network models with just a few lines of code - Moocarme, Matthew (Packt Publishing Limited, 2020)
bDiscover how to leverage Keras, the powerful and easy-to-use open source Python library for developing and evaluating deep learning models/bh4Key Features/h4ulliGet to grips with various model evaluation metrics, including sensitivity, specificity, and AUC scores/liliExplore advanced concepts such as sequential memory and sequential modeling/liliReinforce your skills with real-world development, screencasts, and knowledge checks/li/ulh4Book Description/h4New experiences can be intimidating, but not this one! This beginner's guide to deep learning is here to help you explore deep learning from scratch with Keras, and be on your way to training your first ever neural networks.What sets Keras apart from other deep learning frameworks is its simplicity.
Keywords: COMPUTERS / Intelligence (AI) & Semantics; COMPUTERS / Neural Networks